The influence of the training process on the development of flexibility of the swimmer’s shoulder girdle - Grigan S.A.; Neshcheret N.N.; Khilchevskaya I.V.; Plotnikova A.P. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluate the influence of the training process on the development of flexibility of the swimmer’s shoulder girdle. Methods and structure of the study. The experiment involved 168 swimmers from the “Ekran” Youth Sports School (86 girls, average age 17 years and 82 boys, average age 18 years). Swimmers were tested for shoulder flexibility in preparation for the winter competitive season. After 6 months, the swimmers were surveyed about pain throughout the season. Results and conclusions. The findings showed a strong correlation between poor anterior shoulder flexibility and subsequent shoulder pain. Further research suggests that resistance training increases the likelihood of pain in men as a result of tendon hypertrophy. For flexibility, the occurrence of pain was independent of stroke, distance, or gender, with one exception: at a given level of flexibility, butterfly swimmers were more likely to suffer this injury than others.